Repeated hepatectomy after ALPPS for recurrence of colorectal liver metastasis: the edge of limits?. Issue 10 (October 2021) - Reese, Tim; Makridis, Georgios; Raptis, Dimitri; Malagó, Massimo; Hernandez-Alejandro, Roberto; Tun-Abraham, Mauro; Ardiles, Victoria; de Santibañes, Eduardo; Fard-Aghaie, Mohammad; Li, Jun; Kuemmerli, Christoph; Petrowsky, Henrik; et al.
Abstract: Background: Repeated liver resections for the recurrence of colorectal liver metastasis (CRLM) are described as safe and have similar oncological outcomes compared to first hepatectomy. Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) is performed in patients with conventionally non-resectable CRLM. Repeated resections after ALPPS has not yet been described. Methods: Patients that underwent repeated liver resection in recurrence of CRLM after ALPPS were included in this study. The primary endpoint was morbidity and secondary endpoints were mortality, resection margin and survival. Results: Thirty patients were included in this study. During ALPPS, most of the patients had classical split (60%, n = 18) and clearance of the FLR (77%, n = 23). Hepatic recurrence was treated with non-anatomical resection (57%, n = 17), resection combined with local ablation (13%, n = 4), open ablation (13%, n = 4), segmentectomy (10%, n = 3) or subtotal segmentectomy (7%, n = 2). Six patients (20%) developed complications (10% minor complications). No post-hepatectomy liver failure or perioperative mortality was observed. One-year patient survival was 87%. Five patients received a third hepatectomy. Conclusion: Repeated resections after ALPPS for CRLM in selected patients are safe and feasible with low morbidity and no mortality. Survival seems to be comparable with repeated resections after conventional hepatectomy.